Keanekaragaman Tumbuhan Herba Berpotensi Obat Di Daerah Aliran Sungai Kambata Tana Kabupaten Sumba Timur Sebagai Media Pembelajaran Biologi - Eut, Felitas Rambu Ema; Ina, Anita Tamu (CV. ITTC INDONESIA, 2023)
This study aims to determine the diversity of herbaceous plants with medicinal potential and the use of plants as learning media in the form of flipbooks. This type of research is ecological research with a quantitative approach. Based on the research results, it is known that the diversity of herbaceous plants in the Kambata Tana river is classified as moderate with an H'= 2.212. Analysis of other ecological indices such as density is known to be the largest density by Stachytarpheta jamaicensis with a relative density (KR) value of 19.5% while the smallest density is by Amaranthus spinosus which has a relative density (KR) value of 2.2%, the highest species frequency is owned by Stachytarpheta jamaicensis which has a relative frequency value of 8.73% while Amaranthus spinosus has the smallest species frequency with a relative frequency value of 0.48% and a dominance index of herbaceous plants with medicinal potential of 0.061 which is relatively low. The diversity of herbaceous plants with medicinal potential is used as a learning medium in the form of flipbooks which obtain an average validation value of 96% and are classified as very valid.